2020
DOI: 10.1101/2020.06.21.20132449
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Intrafamilial Exposure to SARS-CoV-2 Induces Cellular Immune Response without Seroconversion

Abstract: Background. In the background of the current COVID-19 pandemic, serological tests are being used to assess past infection and immunity against SARS-CoV-2. This knowledge is paramount to determine the transmission dynamics of SARS-CoV-2 through the post pandemic period. Several individuals belonging to households with an index COVID-19 patient, reported symptoms of COVID-19 but discrepant serology results. Methods. Here we investigated the humoral and cellular immune responses against SARS-CoV-2 in seven fami… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
103
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(110 citation statements)
references
References 15 publications
7
103
0
Order By: Relevance
“…Investigating immune responses to SARS-CoV-2 across all age groups is key to understanding disease susceptibility, severity determinants, and vaccine candidates. Detailed investigations of immune responses during SARS-CoV-2 infection have been reported in adults [10][11][12] , with exposure to SARS-CoV-2 causing speci c T cell responses without seroconversion 13 . Data on immune responses in children exposed to SARS-CoV-2 are limited.…”
Section: Mainmentioning
confidence: 99%
“…Investigating immune responses to SARS-CoV-2 across all age groups is key to understanding disease susceptibility, severity determinants, and vaccine candidates. Detailed investigations of immune responses during SARS-CoV-2 infection have been reported in adults [10][11][12] , with exposure to SARS-CoV-2 causing speci c T cell responses without seroconversion 13 . Data on immune responses in children exposed to SARS-CoV-2 are limited.…”
Section: Mainmentioning
confidence: 99%
“…Notably, the four seasonal common cold-causing human coronaviruses and the zoonotic Middle East respiratory syndrome (MERS) and SARS coronaviruses typically elicit poorly-sustained nAb responses, putatively enabling subsequent re-infection 6 . However, somewhat more durable T cell responses are induced, which in animal models can prevent development of severe disease on challenge, providing a rationale for vaccine-mediated induction of T cell as well as nAb responses 7,8,9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…Isotype analysis yielded similar observations to those made in young healthy mice, with AMP-CpG driving more Th1, IgG2bc-dominant responses compared with soluble CpG or alum, which yielded more balanced or Th1, IgG1-biased profiles ( Figure 9D-G SARS-CoV-2 neutralizing antibody responses to infection are temporary, declining quickly after recovery 16 . In addition, recent studies have shown that a subset of patients recover from COVID-19 with SARS-CoV-2 specific T cells but not neutralizing antibodies 8,9,10 , indicating a potentially important role for T cells as a mechanism of disease prevention or mitigation. Indeed, in mouse models, CD8 + and CD4 + T cells were necessary for protective immunity against SARS and MERS infections 42,43 .…”
Section: Humoral Immune Response Spike Rbd-specific Antibody Responsmentioning
confidence: 99%
“…An optimal SARS-CoV-2 vaccine should generate potent T cell immunity alongside neutralizing antibody responses. Patient recovery from SARS-CoV-2 infection without mechanical ventilation is significantly associated with elevated T cell levels 4,5,6,7 , and T cell responses without humoral responses have proven sufficient for COVID-19 resolution 8,9,10 . Conversely, death has been associated with reduced T cell numbers in COVID-19 11 , with lymphocyte subset analyses implicating deficiency in both CD3 + CD4 + and CD3 + CD8 + T cells 4 .…”
Section: Introductionmentioning
confidence: 99%